Production Decline Analysis and Hydraulic Fracture Network Interpretation Method for Shale Gas with Consideration of Fracturing Fluid Flowback Data - Jianfeng Xiao; Xianzhe Ke; Hongxuan Wu (Geofluids)
After multistage hydraulic fracturing of shale gas reservoir, a complex fracture network is formed near the horizontal wellbore. In postfracturing flowback and early-time production period, gas and water two-phase flow usually occurs in the hydraulic fracture due to the retention of a large amount of fracturing fluid in the fracture. In order to accurately interpret the key parameters of hydraulic fracture network, it is necessary to establish a production decline analysis method considering fracturing fluid flowback in shale gas reservoirs. On this basis, an uncertain fracture network model was established by integrating geological, fracturing treatment, flowback, and early-time production data. By identifying typical flow-regimes and correcting the fracture network model with history matching, a set of production decline analysis and fracture network interpretation method with consideration of fracturing fluid flowback in shale gas reservoir was formed. Derived from the case analysis of a typical fractured horizontal well in shale gas reservoirs, the interpretation results show that the total length of hydraulic fractures is 4887.6 m, the average half-length of hydraulic fracture in each stage is 93.4 m, the average fracture conductivity is 69.7 mD·m, the stimulated reservoir volume (SRV) is 418×104 m3, and the permeability of SRV is 5.2×10−4 mD. Compared with the interpretation results from microseismic monitoring data, the effective hydraulic fracture length obtained by integrated fracture network interpretation method proposed in this paper is 59% of that obtained from the microseismic monitoring data, and the effective SRV is 83% of that from the microseismic monitoring data. The results show that the fracture length is smaller and the fracture conductivity is larger without considering the influence of fracturing fluid.